About stages of distinguishing as a thought operation - Garbačiauskienė, M. (Psichologija, 1966)
The article analyzes how thought activity is changing gradually while disclosing a greater difference between complex and similar objects. Major stages of distinguishing are determined based on the relations of thought operations with an inverse operation – assimilation. A more complex relation between these operations is a higher and distinguishing stage.While comparing the material of various individual stating experiments, the attention was only on these stages which are common in the development of distinguishing, but have different content (grammatical and psychological) terms. It is (1) a line-up (when distinguishing is not based on similarities yet), (2) setting against, (3) comparison (when the difference is determined based on the initial object comparison and search of a common feature), and (4) determining the difference based on the essential similarity based. Clearly, the more complex is the difference relation between objects, the more complex and longer is distinguishing.
Keywords: thinking; thought operations; distinguishing